Identification of Spices Traded in Several Markets in Tobelo City - Silwanus P. Hunsam; Ariance Yeane Kastanja; Zeth Patty (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study aims to identify the types of spices sold in the market and the plant parts used in this trade. The research was carried out in four main markets in Tobelo City, namely Pasar Buale, Pasar Modern, Pasar Rawajaya, and Pasar Wosia. The study took place from May to August 2025. The method used was a survey involving direct observation and interviews with traders using purposive sampling technique. The data obtained were analyzed quantitatively by calculating frequency distribution and percentages. The results show there are 23 types of spices from 12 different plant families. These spices are divided into two main categories: dried spices (such as cinnamon, nutmeg, clove, pepper, and coriander) and fresh spices (such as the rhizome group, citrus, chili, and aromatic vegetables). The Zingiberaceae family has the highest species diversity (5 species), followed by Amaryllidaceae (3 species). Comparisons between locations indicate an uneven distribution of diversity: Pasar Modern has the highest level of diversity with 13 types of spices, followed by Pasar Wosia (11 types), Pasar Rawajaya (7 types), and Pasar Buale (6 types). Based on the frequency distribution of the number of types sold, there are different patterns; the majority of dried spice traders sell a limited variety of between 1–5 types, while fresh spice traders tend to offer a more complete variety ranging from 11–15 types of spices to meet consumers’ daily seasoning needs. The use of plant parts is highly varied, including bark, flower buds, fruit, seeds, rhizomes, leaves, and bulbs.